Case report: ALK D1225N missense mutation in lung adenocarcinoma responds to tyrosine kinase inhibitors - Chen, Jianxin; Wang, Junhui (Frontiers in Pharmacology, 2023)
ALK gene missense mutations are conventionally considered non-driver mutations without pathological significance and, therefore, there is a lacking of effective target drugs against them. The standard treatment option for patients with ALK missense mutations is chemotherapy with or without antiangiogenic agents, which usually results in unsatisfactory outcomes. Herein, we present the case of a patient with metastatic lung adenocarcinoma harboring the only missense mutation in ALK D1225N responding to two ALK-tyrosine kinase inhibitors (TKIs), namely, crizotinib and ensartinib. Our case